Definition of the Essence and the Main Features of Multimodal Transport ("Journal "U". Economy. Management. Finance.", 2017)
This article examines the basic concepts of multimodal transport, reveals the terminology of the presented mode of freight transportation. In this article, a comparative analysis of mixed, multimodal, intermodal transportations is carried out, and the main features of this type of movement of material resources are determined. The conclusion of the article presents results of the research work.
Keywords: multimodal transport; direct multimodal transport; international transport; intermodal; combined transport